Adventures of Captain Underpants the first epic novel - Pilkey, Dav; Garibaldi, Jose; Dzioba, Wes (New York, NY Scholastic Inc., 2023)
When George and Harold hypnotize their principal into thinking that he is the superhero Captain Underpants, he leads them to the lair of the nefarious Dr. Diaper.
"With all new Dog Man comic"--Cover.
Bonus content: The origin of Captain Underpants -- Bonus comix (never-before-seen historical artifacts by George and Harold). Captain Underpants meets Dog Man ; Dog Man and the league of misfits -- Fun facts.
111292
Keywords: Beard, George -- (Fictitious character) -- Juvenile fiction; Hutchins, Harold -- (Fictitious character) -- Juvenile fiction; Captain Underpants -- (Fictitious character) -- Juvenile fiction; School principals -- Juvenile fiction; Schools -- Juvenile fiction; Elementary schools -- Juvenile fiction; Heroes -- Juvenile fiction; Humorous fiction; Juvenile works